Synthesis and biological evaluation of novel ferrocene–naphthoquinones as antiplasmodial agents - García Barrantes, Pedro M. (2013)
This work deals with the synthesis and evaluation of new compounds designed by combination of 1,4-naphthoquinone and ferrocene fragments in a 3-ferrocenylmethyl-2-hydroxy-1,4-naphthoquinone arrangement. A practical coupling reaction between 2-hydroxy-1,4-naphthoquinone and ferrocenemethanol derivatives has been developed. This procedure can be carried out “on-water”, at moderate temperatures and without auxiliaries or catalysts, with moderate to high yields. The synthesized derivatives have shown significant in vitro antiplasmodial activity against chloroquine-sensitive and resistant Plasmodium falciparum strains and it has been shown that this activity is not related to the inhibition of biomineralization of ferriprotoporphyrin IX. Binding energy calculations and docking of these compounds to cytochrome b in comparison with atovaquone have been performed.